PENGARUH JENIS MEDIA TANAM TERHADAP HASIL PERTUMBUHAN DAUN AFRIKA (Vernonia amygdalina Del.) DENGAN METODE STEK BATANG - Cahyani, Zuhrotin; Tyastirin, Esty; Mudalianah, Siti (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study was to determine the effect of planting media on the growth of African leaf stem cuttings (Vernonia amygdalina Del.). This study was an experimental study. There were independent and dependent variables. The growth parameters of plant stem cuttings including the number of leaves, leaf area, and branch height were dependent variables. The type of planting media used (soil, rice husks and manure were independent variables. The design of this study used a completely randomized design (CRD) consisting of 3 treatments, namely soil, rice husks (1:1). Soil, rice husks, and manure with a ratio of (1:1:1). Soil, rice husks, and manure and (2:3:1). The data analysis technique used the ANOVA test. The results showed that the planting media had no significant effect on the growth of African leaf stem cuttings (Vernonia amygdalina Del.) with a significance value of > 0.05.